Do-Not-Resuscitate Orders in Fatal Toxic Exposures: A Poison Center’s Review - Dilani Weerasuriya; Sophia Sheik; Brent W. Morgan (Western Journal of Emergency Medicine, 2012)
Introduction: Self-exposure is a leading method for suicide both in the United States and worldwide and thus is a major preventable public health issue. Surrogate decision makers are tasked with making medical decisions for the patient while keeping the patient’s wishes in mind. Decisions related to code status become more complicated when the patient’s situation is the result of a suicidal act. The objectives were to 1) determine how frequently Do Not Resuscitate orders (DNR orders) are placed for the intentionally self-exposed (ISE) patient using the Regional Poison Control Center (RPCC) data, and 2) identify if DNR orders in intentionally self-exposed patients were placed before or afterdevelopment of poor prognostic signs.Methods: We analyzed all exposure-related deaths reported to the RPCC from January 1, 2000 to December 31, 2010. We reviewed data for the following: exposure intent, exposure substance, outcome, age, code status, date of DNR/withdrawal of care order, previous suicide attempts, and poor prognostic signs.Results: Of the 476 total deaths, nearly half were the result of an intentional self-exposure (n= 235; 49.4%). Most deaths, when code status was reported, had advanced cardiac life support, or “fullcodes” (n=131; 55.6%). Of the total deaths with a DNR or withdrawal of care order (n=104), over half were from an ISE (n=55; 52.9%). A higher percentage of the ISEs had a DNR order/withdrawal of careorder; however, it was not a statistically significant difference OR 1.23 (95% CI 0.64, 2.37). Regardless of intent, patients treated as full codes were on average 19.5 years younger than the DNR orders group. Only 2 DNR orders were placed prior to development of poor prognostic signs. Unintentional self-exposures consumed a mean of 1.4 substances (range 1 to 4). ISEs consumed a mean of 2.3 substances (range 1 to 19).Conclusion: People are often asked to make life-and-death decisions for a loved one. The nature of the exposure can complicate the issue if the exposure has an antidote or is known to have a limited effect. Further study is needed to assess the extent of these cases and to identify optimal management guidelines or policy to aid both the medical teams caring for these patients and the surrogate decision makers. [West J Emerg Med. 2012;13(3):294-297.]